2020
DOI: 10.1007/s12975-020-00839-4
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of Early Administration of Apixaban on Clinical Outcomes in Patients with Acute Large Vessel Occlusion

Abstract: Early administration of direct oral anticoagulants in patients with acute large vessel occlusion (LVO) and nonvalvular atrial fibrillation (NVAF) is a concern, as endovascular therapy (EVT) became highly utilized. We conducted a historical and prospective multicenter registry at 38 centers in Japan from July 2016 to February 2018. Patients aged ≥ 20 years with NVAF and acute LVO or stenosis who received apixaban within 14 days from onset were included. We compared patients who received apixaban < 48 h (Earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Moreover, larger infarctions carry a heightened potential risk of sHT (4,22). In a previous observational study, the early use of apixaban within 2 days in AF stroke with concurrent large vessel occlusion demonstrated comparable safety to later use (23). However, dosing considerations arise for early apixaban initiation in patients with medium to large lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, larger infarctions carry a heightened potential risk of sHT (4,22). In a previous observational study, the early use of apixaban within 2 days in AF stroke with concurrent large vessel occlusion demonstrated comparable safety to later use (23). However, dosing considerations arise for early apixaban initiation in patients with medium to large lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have also reported outcomes according to anticoagulation timing (Supplementary Table 1). Collectively, these studies suggest that early anticoagulation with a NOAC is not associated with a high risk of intracranial haemorrhage, and that this risk is low compared to that of recurrent ischaemic stroke (77)(78)(79)(80)(81)(82)(83). Unexpectedly, several studies of these studies found numerically higher intracranial haemorrhage rates with more delayed anticoagulation, or similar or higher rates of recurrent ischaemia in early treatment groups (80)(81)(82)(83).…”
Section: Current Evidencementioning
confidence: 95%
“…Collectively, these studies suggest that early anticoagulation with a NOAC is not associated with a high risk of intracranial haemorrhage, and that this risk is low compared to that of recurrent ischaemic stroke (77)(78)(79)(80)(81)(82)(83). Unexpectedly, several studies of these studies found numerically higher intracranial haemorrhage rates with more delayed anticoagulation, or similar or higher rates of recurrent ischaemia in early treatment groups (80)(81)(82)(83). Given substantial imbalances in stroke severity, size and the presence of haemorrhagic transformation between groups, these results are likely to be confounded by treatment bias.…”
Section: Current Evidencementioning
confidence: 99%
“…ALVO, which took place at 38 centers in Japan from July 2016 to February 2018, is a historical and prospective multicenter registry that recruited acute stroke patients with LVO or intra-/extracranial artery stenosis (>50%) who initiated apixaban within 14 days after the onset of NVAF. The full eligibility criteria have been previously published [18]. We included peripheral artery occlusions such as M2-3, A1-2, or P1-2.…”
Section: Methodsmentioning
confidence: 99%
“…In the Apixaban on clinical outcome of patients with Large Vessel Occlusion or stenosis (ALVO) trial, we reg-istered NVAF patients with acute LVO or intra-/extracranial artery stenosis (more than 50% stenosis) who were administered a DOAC (apixaban) within 14 days after onset and followed them for 1 year [18]. Many NVAF patients included in this study had only acute LVO, but some NVAF patients had intra-/extracranial artery stenosis.…”
Section: Introductionmentioning
confidence: 99%